2023
DOI: 10.3390/horticulturae9020221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Root and Foliar Application of Corn Steep Liquor on Pepper Plants: A Physiological, Nutritional, and Morphological Study

Abstract: The industrial washing of corn grain during its milling generates a residue known as “corn steep liquor (CSL)”. This residue is rich in amino acids, carbohydrates, vitamins, and mineral nutrients that can stimulate the vegetative growth when applied to plants. However, the mode of action of this product is not yet known. This work involved the foliar and root application to pepper plants, at a dose of 5 mL L−1, of two CSL products (CSL-H and CSL-B), which differ in the way they have been stabilized. In both ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Additionally, carotenoids, functioning as antioxidants, may protect plants from the effects of reactive oxygen species [ 35 ]. Navarro-Morillo et al demonstrated that the exogenous root application of CSL alleviated the adverse impact of salt stress on plant photosynthesis [ 11 ]. Similarly, MI enhanced photosynthesis in plants by increasing the content of photosynthetic pigments and stomatal conductivity [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, carotenoids, functioning as antioxidants, may protect plants from the effects of reactive oxygen species [ 35 ]. Navarro-Morillo et al demonstrated that the exogenous root application of CSL alleviated the adverse impact of salt stress on plant photosynthesis [ 11 ]. Similarly, MI enhanced photosynthesis in plants by increasing the content of photosynthetic pigments and stomatal conductivity [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corn steep liquor (CSL), a concentrated byproduct from corn starch production, is an acidic viscous liquid rich in various nutrients, including amino acids, sugars, proteins, vitamins, and minerals [ 10 ]. The diverse nutritional composition of CSL allows for versatile applications across various fields, such as additives in biotechnological production media, animal feed, surfactant production, and a component in biostimulants [ 11 ]. The presence of bioactive molecules such as organic acids and plant growth regulators in CSL provides a basis for its use in soil improvement and biostimulant research [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…AAs were extracted and analyzed using a UHPLC system equipped with a fluorescence detector following the method described by Navarro‐Morillo et al (2023). AAs concentrations were expressed as μg g −1 DW.…”
Section: Methodsmentioning
confidence: 99%
“…Indoleacetic acid (IAA), gibberellins (GA, GA1 + GA3 + GA4), cytokinins [CKs: trans‐zeatin (tZ) + isopentenyl adenine (iP)], ABA, aminocyclopropane carboxylic acid (ACC, as precursor of ethylene), SA, and jasmonic acid (JA) were analyzed as described by Navarro‐Morillo et al (2023) using a U‐HPLC‐MS system. The concentration of phytohomones was expressed as ng g −1 DW.…”
Section: Methodsmentioning
confidence: 99%
“…A "shoulder" precedes the maximum OTR of 17 mmol/L/h, after which a drop in OTR was observed, indicating the depletion of the initial carbon source. Since carbon is not abundant in pure CSL, 14,58 the formation of overflow metabolites is not expected. As a result of the consumption of lactate, as well as proteins and amino acids in CSL, 1,44,45 the final pH value was increased (Figure 4b).…”
Section: Metabolic Activity Of Bacillus Subtilis On Lband Csl-based M...mentioning
confidence: 99%